Human milk microbiota and oligosaccharides in colostrum and mature milk: comparison and correlation - Ge, Hongda; Zhu, Wenxiu; Zhang, Jing; Wang, Zijing; Shi, Huijing; Sun, Jie; Shi, Ming (Frontiers in Nutrition, 2024)
The interaction between the human breast milk microbiota and human milk oligosaccharides (HMOs) plays a crucial role in the healthy growth and development of infants. We aimed to clarify the link between the breast milk microbiota and HMOs at two stages of lactation.The microbiota and HMOs of 20 colostrum samples (C group, 1-5 days postpartum) and 20 mature milk samples (S group, 42 days postpartum) collected from postpartum mothers were analyzed using 16S rRNA gene high-throughput sequencing and high-performance liquid chromatography-tandem mass spectrometry.The total average HMO content was significantly higher in the C group than in the S group (6.76 ± 1.40 g/L vs 10.27 ± 2.00 g/L, P < 0.05). Among the HMOs, the average values of 2′fucosyllactose (2′-FL, 1.64 ± 1.54 g/L vs 3.03 ± 1.79 g/L), 3′-sialyllactose (3′-SL, 0.10 ± 0.02g/L vs 0.21 ± 0.06), 6′-SL (0.22 ± 0.09 g/L vs 0.33 ± 0.11 g/L), and lacto-N-triaose 2 (LNT2, 0.03 ± 0.01 g/L vs 0.16 ± 0.08 g/L) were significantly lower in the S group than in the C group (P < 0.05), while that of 3′-FL was significantly higher in the S group than in the C group (1.35 ± 1.00 g/L vs 0.41 ± 0.43 g/L, P < 0.05). The diversity and structure of the microbiota in the S and C groups were also significantly different (P < 0.05). Comparative analysis of the microbial communities revealed that Proteobacteria and Firmicutes were the most abundant phyla, in both groups, with the keystone species (Serratia, Streptococcus and Staphylococcus) of breast milk closely interacting with HMOs, including 3′-SL, 6′-SL, and LNT2. In PICRUSt2 functional prediction analysis, the S group exhibited significant reduction in the expression of genes involved in several infectious disease pathways. Discussion: Our findings support the recognition of human milk as a synbiotic comprising beneficial bacteria and prebiotic HMOs.